2020
DOI: 10.1155/2020/5759182
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in the Unfolded Protein Response in the FGR Rat Pancreas

Abstract: Accumulating evidence suggests that fetal growth restriction (FGR) leads to the development of diabetes mellitus in adults. The aim of this study was to investigate the effect of protein malnutrition in utero on the pancreatic unfolded protein response (UPR) pathway in FGR offspring. An FGR model was developed by feeding a low-protein diet to pregnant rats throughout gestation. Eighty-four UPR pathway components in the pancreas were investigated by quantitative PCR arrays and confirmed by qPCR and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Examination of pancreata by transmission electron microscopy further revealed the presence of autophagosomes in islet -cells, while mTORC protein levels were also decreased relative to control offspring [83]. Conversely, another study found LC3BII and Beclin1 protein abundance to be decreased in the IUGR fetal pancreas following protein restriction [82]. These findings were not expected by the authors of the study; however, they speculated that autophagy may have been suppressed due to decreased phosphorylation of AMPK [82].…”
Section: Autophagymentioning
confidence: 73%
See 3 more Smart Citations
“…Examination of pancreata by transmission electron microscopy further revealed the presence of autophagosomes in islet -cells, while mTORC protein levels were also decreased relative to control offspring [83]. Conversely, another study found LC3BII and Beclin1 protein abundance to be decreased in the IUGR fetal pancreas following protein restriction [82]. These findings were not expected by the authors of the study; however, they speculated that autophagy may have been suppressed due to decreased phosphorylation of AMPK [82].…”
Section: Autophagymentioning
confidence: 73%
“…Conversely, another study found LC3BII and Beclin1 protein abundance to be decreased in the IUGR fetal pancreas following protein restriction [82]. These findings were not expected by the authors of the study; however, they speculated that autophagy may have been suppressed due to decreased phosphorylation of AMPK [82]. It was also noted that the whole pancreas was used for molecular analyses, and the authors acknowledged that the endocrine and exocrine pancreas are affected differently by the in utero environment.…”
Section: Autophagymentioning
confidence: 85%
See 2 more Smart Citations
“…Given that ER stress is linked to glucose intolerance and insulin resistance, it seems appropriate that IUGR offspring exhibit activation of the UPR in additional organs involved in glucose homeostasis. Much like the liver, gestational exposure to a low protein diet leads to activation of all three UPR pathways in the pancreas; however, this was exclusive to the fetal pancreas at ED20 [81]. Fetal pancreata displayed increased Atf4/6, protein kinase R-like endoplasmic reticulum kinase (PERK), Xbp-1, p-eIF2α, and cAMP responsive element-binding protein-3-like 3 (Creb3l3), while adult offspring only had upregulation of Atf6 and Creb3l3 [81].…”
Section: Endoplasmic Reticulum (Er) Stress and The Unfolded Protein Responsementioning
confidence: 99%